Representações sociais de masculinidades entre homens sírios em situação de refúgio no Brasil - Valle, Gabriela Viol (2023)
Through this research, the objective was to investigate identity representations in the context of masculinities among Syrian men in refugee situations in Brazil. The methodological strategies that underlie this research are of a qualitative nature and data were collected through individual interviews, carried out online, synchronously, through the video platforms of Google Meet and Zoom. The sample consisted of Syrian men who have been in temporary refuge situations in Brazil for at least four years, aged between 25 and 43 years. The interviews, carried out with the aid of a semi-structured script, were recorded and transcribed, with the authorization of the participants via the Free and Informed Consent Form. Data treatment and analysis were performed through content analysis. In the results, contents related to (i) the experiences of social insertion of the subjects in refugee situations in Brazil were identified, which include elements related to: their interpersonal relationships, such as friendship, love relationship, family, relations with Brazilians and the importance of the Portuguese language in the interactions; work, both in Brazil and in Syria; religion, which includes elements related to conflicts, groups and religious beliefs/disbeliefs; prejudices and stereotypes, which result in generalizations and discrimination directed at Syrians; and (ii) masculinity and gender, including elements associated with: practices of masculinity with regard to being a man in general, in Brazil and in Syria; conceptions of masculinity, such as hegemonic, pluralized and homoaffective; and comparisons between male and female genders, such as aspects of equality and gender differences. From the results, issues related to the insertion of participants in Brazil were discussed, as well as their identity processes while being in a new country, with new sociocultural practices, as well as aspects related to the social representations of masculinity of Syrian individuals in temporary refuge situations.